Investigation of crack paths in natural fibre-reinforced composites (Fracture and Structural Integrity, 2015)
Nowadays, fibre-reinforced composite materials are widely used in many fields, e.g. automotive and aerospace. Natural fibres such as flax and hemp provide good density specific mechanical properties. Additionally, the embodied production energy in natural fibres is much smaller than in synthetic ones. Within this paper the fracture mechanical behaviour of flax fibre-reinforced composites is discussed. Especially, this paper focuses on the determination and investigation of crack paths in compact tension specimens with three different fibre directions under a static as well as fatigue load. Differences and similarities in the obtained crack paths under different loading conditions are presented. Due to the pronounced orthotropic behaviour of those materials the crack path is not only governed by the stress state, but practically determined by the fibre direction and fibre volume fraction. Therefore, the well-known stress intensity factor solutions for the standard specimens are not applicable. It is necessary to carry out extensive numerical simulations to evaluate the stress intensity factor evolution along the growing crack in order to be able to determine fatigue crack growth rate curves. Those numerical crack growth simulations are performed with the three-dimensional crack simulation program ADAPCRACK3D to gain energy release rates and in addition stress intensity factors.
Keywords: Natural fibre-reinforced composites